Die teoloog as akademiese saboteur - Du Plessis, J. G. (Verbum et ecclesia, 1990)
The theologian as academical ‘agent provocateur’ Some thoughts on the relation between Biblical science and the role of traditional Christian beliefs in everyday life. What the Biblical scientist teaches in the university is - and should be seen to be - relevant to the way the Christian tradition is supposed to shape everyday life. The Biblical scientist should live in constant dialogue between classical Christianity and the modern secularist world view in which Biblical science shares to a lesser or larger extent. The essay argues that the Biblical scientist should take classical Christianity as his point of departure. This entails a "theology in exile" within the academic community.